The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1111/j.1468-3083.2004.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Extensive nodular cutaneous amyloidosis: an unusual presentation

Abstract: Amyloidosis is characterized by the deposition of a group of unrelated proteins leading to changes in tissue architecture and function. The nodular variant is the rarest form of the cutaneous amyloidoses. We report a patient with localized nodular amyloidosis without systemic amyloid involvement or paraproteinaemia after 6 years of follow-up. The unusual aspects of our case were a plaque presentation rather than nodular, and the disseminated pattern observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Three other patients had "multiple skin lesions" without a clear description of the locations [1]. There are three case reports, which describe disseminated lesions or new lesions spreading to non-contiguous locations over two to 6 years without monoclonal proteins [6,7,8 ].…”
Section: Case Discussionmentioning
confidence: 99%
“…Three other patients had "multiple skin lesions" without a clear description of the locations [1]. There are three case reports, which describe disseminated lesions or new lesions spreading to non-contiguous locations over two to 6 years without monoclonal proteins [6,7,8 ].…”
Section: Case Discussionmentioning
confidence: 99%
“…4,7 On histopathological examination, the amyloid material is found within the superficial papillary dermis. 2,4,8,9 Rarely, it may be atrophic or bullous in appearance. Nodular (tumefactive) amyloidosis may be localized or systemic and is derived from immunoglobulin light chains (AL).…”
Section: Discussionmentioning
confidence: 99%
“…Single or multiple nodules are the usual lesions seen, and large plaques as in this case, are exceptional. 2 Initial reports suggested that there was a 50% progression of NTA to systemic disease, 3 whereas recent studies were more encouraging, with only 7% progression on prolonged follow-up. 4 However, one case in this latter series showed systemic progression only after 20 years of surveillance.…”
Section: P Dmentioning
confidence: 99%